Empowering Women-Led MSMEs: A Mediation Analysis of Entrepreneurial Self-Efficacy in the Relationship Between Market Orientation, Digital Capability, and Business Performance (A Case Study of Women Entrepreneurs in HIPPI Medan) - Erwansyah Erwansyah; Maya Macia Sari (Journal of Management, Economic, and Accounting, 2025)
This study aims to analyze the influence of Market Orientation and Digital Capability on Business Performance among women-led MSMEs, with Entrepreneurial Self-Efficacy (ESE) examined as a mediating construct. Using a quantitative approach, data were collected from female entrepreneurs and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both direct and indirect relationships. The findings reveal that Market Orientation and Digital Capability significantly and positively affect ESE, indicating that market-driven strategic behavior and the ability to utilize digital tools enhance entrepreneurial confidence. Moreover, Digital Capability shows the strongest direct effect on Business Performance, while the effect of Market Orientation is positive but relatively smaller. Mediation analysis demonstrates that ESE significantly transmits the effects of both Market Orientation and Digital Capability on Business Performance, highlighting the critical psychological mechanism through which cognitive and strategic capabilities translate into improved business outcomes. The study contributes to the literature by reinforcing the role of self-efficacy as a central pathway in women’s entrepreneurship performance models. Practically, the results underscore the importance of capacity-building initiatives focused on digital skills, market literacy, and psychological empowerment to strengthen the competitiveness of women-led MSMEs in an increasingly digital economy.